2013
DOI: 10.1111/phn.12072
|View full text |Cite
|
Sign up to set email alerts
|

Recidivism after Release from a Prison Nursery Program

Abstract: Objective To analyze three-year recidivism after release from a prison nursery, a secure unit that allows imprisoned women to care for their infants. Design and Sample Descriptive study of 139 women who co-resided with their infants between 2001–2007 in X prison nursery. Measurement Administrative criminal justice data were analyzed along with prospective study data on demographic, mental health, and prison nursery policy-related factors. Results Results reflect a sample of young women of color with hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
0
24
0
4
Order By: Relevance
“…Documentaries feature testimonials from women who describe, through tears, how being able to bond with their babies despite, or in some cases in spite of, being in prison changed their lives, helped them parent and gave them confidence (McShane, 2011). Research studies have reported that women in these programmes have lower recidivism rates (Goshin et al, 2014). Such reports project a synergism and idealism in the ability of parenting and incarceration to assist a mother in transformation to someone who is an upstanding citizen and a ‘worthy’ mother.…”
Section: Reaffirming Normative Motherhood Through Incarcerationmentioning
confidence: 99%
“…Documentaries feature testimonials from women who describe, through tears, how being able to bond with their babies despite, or in some cases in spite of, being in prison changed their lives, helped them parent and gave them confidence (McShane, 2011). Research studies have reported that women in these programmes have lower recidivism rates (Goshin et al, 2014). Such reports project a synergism and idealism in the ability of parenting and incarceration to assist a mother in transformation to someone who is an upstanding citizen and a ‘worthy’ mother.…”
Section: Reaffirming Normative Motherhood Through Incarcerationmentioning
confidence: 99%
“…The idea is that having the time and space to cultivate their maternal identity will help them refocus away from a life of crime and toward one of normativity. Research publications claim that women who participate in these programs have lower reincarceration rates (Goshin, Byrne, and Henninger 2014). So it seems there is at least indirect evidence that prisons perceive a continued pregnancy to have rehabilitative and crime‐deterring potential, thus serving a penological interest.…”
Section: The Judicialization Of Prison Abortionsmentioning
confidence: 99%
“…Nova York demonstraram que, nos últimos 30 anos, a população carcerária feminina dos Estados Unidos aumentou, tornando-se, assim, um grande problema de saúde pública, pois mais de 60% dessas mulheres presas têm mais de 2 filhos e de 6-10% engravidam nesse contexto (5,7) .…”
Section: Pesquisas Realizadas Em Prisão Do Estado Deunclassified